CHARACTERIZATION OF THE RENIN-ANTIRENIN SYSTEM - Warren, Bert (The Rockefeller University Press, 1966)
Rabbit antibody capable of neutralizing the pressor activity of the enzyme renin, derived from hog kidneys, was characterized with respect to type and capacity to react serologically. Three antirenin antibodies were detected, both a precipitating and nonprecipitating, neutralizing antibody as well as a neutralizing antibody capable of being absorbed by inactivated renin. The precipitating, neutralizing antibody was purified and used successfully in an assay for hog renin by means of a hemagglutination inhibition test. By immunofluorescent methods utilizing the purified antiserum, renin was found to be localized in the macula densa of the distal convoluted tubules and the juxtaglomerular cells of the afferent arteriole in both hog and dog kidneys.